Effects Of Mouthwash And Varnısh Forms Of Antı-Mıcrobıal Agents On Shear Bond Strength Of Orthodontıc Brackets - Tancan Uysal; Ali İhya Karaman (Galenos Yayinevi, 2004)
The purpose of this study was to investigate whether different forms of antimicrobial agents combined with primer applied to etched enamel surfaces will affect the shear bond strength (SBS) and the bracket/adhesive failure modes of metallic orthodontic brackets. Eighty non-carious human premolars were randomly divided into four groups of 20 each. All teeth were embedded in self cure acrylic in a vertical position so that the crowns were exposed. A composite resin (Transbond XT) was used to bond stainless steel brackets. In all groups buccal surfaces of the teeth were etched with 37% phosphoric acid for 30 seconds. Teeth in first group were used as a control and brackets were bonded with standard procedures. For the other three groups, mixtures containing a primer (Transbond XT) and one of three antimicrobial agents were prepared (Klorhex mouthwash in 1:1 ratio, Kloroben mouthwash in 1:1 ratio and Cervitec varnish in 1:2 ratio). These mixtures were applied to the etched enamel surfaces and thoroughly light cured for 20 seconds, and the brackets were bonded and light cured for 40 seconds. The SBS values of these brackets (MPa) were recorded using a universal testing machine. Adhesive Remnant Index (ARI) scores were determined after failure of the brackets. Data were analyzed using analysis of variance (ANOVA), Tukey honestly significant difference (HSD), and chi-square tests. Results of ANOVA revealed statistically significant differences in bond strengths among the various groups tested (p<0.001). The results of the present study demonstrated that Groups 1 (control) and 4 (Cervitec varnish) had higher SBS values than the other applications. Transbond XT primer which had hydrophobic character not mixed with the mouthwash forms of the anti-microbial agents. The bond strength values and the bracket failure rates in Group 2 and 3 are not clinically acceptable. Application of different antimicrobial agents may result in differences in the site of failure.